CGA’S IMPACT ON MORTALITY AND READMISSION COMPARED WITH STANDARD GERIATRIC CARE - Fawwaz Fathur Rahman; Fatih Darmawansyah; Farrel Izzatur Rahim (Journal of Innovation Research and Knowledge, 2025)
The global rise in the older adult population has been accompanied by increasing rates of frailty, multiple chronic conditions, and functional decline, all of which heighten the risk of hospitalization and death. Conventional hospital care often concentrates on treating acute medical issues and may not address the broader and interconnected needs of geriatric patients. Comprehensive Geriatric Assessment (CGA) was introduced as a structured, multidisciplinary approach that evaluates medical status together with functional ability, psychological well-being, social circumstances, and nutritional needs, aiming to develop a more holistic and coordinated plan of care. This review aims to assess the effectiveness of CGA compared with standard care in reducing mortality and hospital readmission among older inpatients. A systematic search was conducted in PubMed, ScienceDirect, and the Cochrane Library for randomized controlled trials published between 2016 and 2025 involving patients aged 60 years and older. Thirty studies met the inclusion criteria and were synthesized narratively. Overall, the evidence showed that CGA did not consistently reduce mortality; however, it demonstrated a favorable effect on lowering readmission rates and improving continuity of care. These variations were influenced by differences in team structure, implementation intensity, and follow-up duration. In conclusion, CGA may enhance the overall quality of geriatric hospital care, although its impact on mortality remains uncertain and warrants further investigation.